MENINGKATKAN HASIL BELAJAR MATA PELAJARAN FIQIH MATERI SHOLAT JAMA’ DAN QOSHOR DENGAN PENDEKATAN KONSTRUKTIVISME PADA SANTRI KELAS IV MADRASAH DINIYAH AS-SA’IDIYAH PPAI AL-IHSAN BULULAWANG MALANG - Achmad Musyadad Al-Arifi; Masykuri Bakri; Moh Murtadho (VICRATINA, 2020)
In the process of learning teaching teachers have a very important role to support students ' learning outcomes in learning. The author wants to uncover how to improve the learning outcomes of the fiqh of prayer material Jama ' and qoshor with constructivism approach in class IV students of Madrasah Diniyah As-Sa'idiyah PPAI Al-Ihsan Bululawang Malang. The methods used in this research are: draft research using qualitative descriptive design.  Data collection techniques include: tests, interviews, observations, and documentation. The data analysis technique used is a qualitative data analysis technique developed by Miles and Huberman, namely with data-on-production, data presentation, conclusion withdrawal, and data ferification from the results of this study is known that,Student Learning Results/students in the class IV Madrasah Diniyah As-Sa'idiyah PPAI Al-Ihsan Bululawang before applied constructivism strategy has not reached the standards of the desired fiqh competence that is 60% or 9 students/student from 15 student/students who have achieved the standard of Fiqh learning results that is 80%. The implementation of Constructivism strategy can improve the learning outcomes of Fiqh prayer materials and Qoshor grade IV students Madrasah Diniyah As-Sa'idiyah PPAI Al-Ihsan Bululawan.